2015
DOI: 10.1007/s00441-015-2296-3
|View full text |Cite
|
Sign up to set email alerts
|

ORC proteins in the mammalian zygote

Abstract: Summary The origin recognition complex (ORC) proteins, ORC1-6, are the first proteins that bind DNA replication origins to mark the competency for the initiation of DNA synthesis. These proteins have complex mechanisms of assembly into the ORC complex, and unexpected localizations in the mitotic chromosomes, cytoplasm, and nuclear structures. The mammalian zygote is a potentially important model that may contribute to our understanding of the mechanisms and features influencing origin establishment, and in ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…F-actin is essential for ARP2 localization and plays a key role in the asymmetric division and polar body extrusion 50 , 51 . ORC4 is a subunit of the origin recognition complex (ORC) but may play a role in the oocyte outside of DNA replication; ORC4 is localized along the oolemma in the GV-oocyte and forms an ovoid structure surrounding the extruding anaphase chromosomes during both meiotic divisions 37 , 52 . In our study, the MII-oocytes from XY females showed similar localization of ORC4, ARP2, and F-actin to those from XX females, suggesting that cortical localization of the MII-spindle and its downstream RanGTP gradient –ARP2/3 pathway was largely normal.…”
Section: Discussionmentioning
confidence: 99%
“…F-actin is essential for ARP2 localization and plays a key role in the asymmetric division and polar body extrusion 50 , 51 . ORC4 is a subunit of the origin recognition complex (ORC) but may play a role in the oocyte outside of DNA replication; ORC4 is localized along the oolemma in the GV-oocyte and forms an ovoid structure surrounding the extruding anaphase chromosomes during both meiotic divisions 37 , 52 . In our study, the MII-oocytes from XY females showed similar localization of ORC4, ARP2, and F-actin to those from XX females, suggesting that cortical localization of the MII-spindle and its downstream RanGTP gradient –ARP2/3 pathway was largely normal.…”
Section: Discussionmentioning
confidence: 99%
“…2020), and also affected the balance of epigenetic regulation (S hen and S pruck 2017). ORC proteins can bind DNA replication origins to initiate DNA synthesis, and ORC is especially important in controlling centriole and centrosome copy number (O rtega et al . 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Dr. Ward with colleagues [115] showed that after fertilization, the ORC1, 2, 3, and 5 proteins localize between the separating maternal chromosomes, while the ORC6 subunit is localized to the periphery of the nucleoli at all zygotic stages. This unexpected distribution of ORC proteins suggest their potential roles in mitosis and chromatin segregation in the mammalian zygote [115]. …”
Section: Neurogenesis and Embriogenesismentioning
confidence: 99%